1996
DOI: 10.1088/0963-0252/5/2/021
|View full text |Cite
|
Sign up to set email alerts
|

A large-area ECR processing plasma

Abstract: This paper describes an improved large-diameter electron cyclotron resonance (ECR) source which employs a strip-bar antenna. By launching a 2.45 GHz microwave near the magnetic field of permanent magnets of alternative polarity set along closed loops, an ECR plasma is produced. The source diameter is 30 cm. The characteristics of an oxygen plasma produced with this modified source are an electron density of 1.4 × 10 11 cm −3 , electron temperature of 3 eV and space potential with respect to the chamber wall of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 6 publications
(8 reference statements)
1
9
0
Order By: Relevance
“…The drift normally to the magnetic lines of force is due to the magnetic field gradient and the finite curvature of the lines of force. Miyazawa et al [9] observed the same cause of drift in a similar multipolar magnet system.…”
Section: The Heating Of Electrons In Distributed Multipolar Magnet Symentioning
confidence: 75%
See 1 more Smart Citation
“…The drift normally to the magnetic lines of force is due to the magnetic field gradient and the finite curvature of the lines of force. Miyazawa et al [9] observed the same cause of drift in a similar multipolar magnet system.…”
Section: The Heating Of Electrons In Distributed Multipolar Magnet Symentioning
confidence: 75%
“…Such magnet systems are very bulky; however, they offer a possibility of simple variation of the magnetic field and of the parameters of magnetic trap. An alternative to electromagnets is provided by strong permanent magnets which are employed, among other things, for developing multipolar magnet configurations [9,10]. The permanent magnets require no source of current and are preferable to electromagnets in numerous applications.…”
Section: Introductionmentioning
confidence: 99%
“…Such magnet systems are very bulky; however, they offer a simple method of varying the magnetic field and the parameters of magnetic trap. An alternative to electromagnets is provided by strong permanent magnets [9,10]. They require no source of current and are preferable to electromagnets in numerous applications; in addition, they enable one to develop systems of distributed plasma sources which provide for adequate uniformity of processing of large surfaces [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Such traps are preferable in many cases as no current source is required. Moreover, permanent magnets allow one to build distributed plasma sources for uniform processing of large areas [8,9].…”
Section: Introductionmentioning
confidence: 99%